Evasion of the Immune System by Mycobacterium tuberculosis: A Special Review on Macrophages - Handayani, Kurnia Maidarmi; Iswanti, Febriana Catur (Universitas Baiturrahmah, 2024)
Mycobacterium tuberculosis, the bacterium that caused tuberculosis, is estimated to affect 10 million people worldwide in 2019. This bacterium is an intracellular pathogen that is spread through the inhalation of bacterial aerosol particles. The innate immune system in the lungs is prepared to phagocytize these bacteria, particularly macrophages, dendritic cells, monocytes, and neutrophils. M. tuberculosis can evade attacks by the host immune system and has developed strategies to infect successfully, especially macrophages. This intracellular bacterium can inhibit phagolysosome fusion, which is associated with lipoarabinomannan (LAM) in the bacterial cell wall. M. tuberculosis also can persist in phagolysosomes by inhibiting acidification and also inhibiting the action of NOX2 from producing ROS. This ability also allows these bacteria to avoid autophagy within macrophages. Knowledge of the power of these bacteria to manipulate and evade the immune system, especially macrophages, is beneficial in developing medicines and vaccines in the future.